Cardiac Morbidity of Carotid Endarterectomy Using Regional Anesthesia Is Similar to Carotid Stent Angioplasty. (November 2013) - Kfoury, Elias; Leng, David; Hashemi, Homayoun; Mukherjee, Dipankar
Carotid artery stenting (CAS) was presented by carotid revascularization endarterectomy versus stenting trial as a minimally invasive approach with less risk of postoperative myocardial infarction (MI) when compared to carotid endarterectomy (CEA). Our study aimed to compare the postoperative MI rate for CAS with CEA under general anesthesia (GA) and local anesthesia (LA). A retrospective study was conducted at our institution comparing CAS with CEA under LA and CEA under GA. Thirty-day postoperative MI and strokes were evaluated for the different subgroups. A total of 1127 procedures were included in the analysis: 421 CEAs under GA, 611 CEAs under LA, and 95 CAS. No significant difference in postoperative MI was encountered between CAS and CEA under LA (0.2% vs 1.1%, P = .25). The CEA under GA was found to have a statistically significant higher risk of MI compared to LA (1.2% vs 0.2%, P = .044). Our evidence suggests that CEA under LA does not have an increased risk of MI compared to CAS.